Environmental Risk Assessment of Sarimukti Landfill Postfire in Indonesia - Widyarsana, I Made Wahyu; Maulidya, Nisrina (International Journal of Integrated Engineering, 2025)
Indonesia aims to ensure that 100% of urban waste is properly managed focusing 80% on waste collection and 20% on reduction, while transitioning toward a processing-based waste management system. Despite various solutions, achieving substantial progress remains difficult. Waste pollution, including unsightly waste, foul odors, and hazardous leachate, negatively impacts the environment. The fire at Sarimukti landfill was caused by careless disposal of cigarette butts during the dry season. Exacerbated the situation and affected more than 15 hectares. Therefore, an environmental quality evaluation using an Integrated Risk-Based Approach (IRBA) is required. According to Ministry of Public Works Regulation Number 03 of 2013, this evaluation is crucial before deciding whether to rehabilitate or close the landfill. This study characterizes waste during a fire disaster, assesses leachate quality in Sarimukti landfill treatment facility, and conducts a rapid environmental assessment using the IRBA method to determine landfill feasibility. The burned waste had an average moisture content of 10.41%, volatile matter of 49.04%, ash content of 50.95%, fixed carbon of 31.05%, and a calorific value of 3,391.19 cal/g. The leachate quality exceeded standards for BOD, COD, and total nitrogen, while pH, TSS, mercury, and cadmium remained within acceptable limits. The final Environmental Risk Index assessment yielded a very high hazard evaluation of 622.24, indicating that the landfill should be closed due to its significant environmental and social impacts.